Turbulent Prandtl Number and its Use in Prediction of Heat Transfer Coefficient for Liquids - Hasan, Basim O. (Nahrain University College of Engineering Journal, 2007)
A theoretical study is performed to determine the turbulent Prandtl number (Prt ) for liquids of wide range of molecular Prandtl number (Pr=1 to 600)under turbulent flow conditions of Reynolds number range 10000- 100000 by analysis of experimental momentum and heat transfer data of other authors. Asemi empirical correlation for Prt is obtained and employed to predict the heat transfer coefficient for the investigated range of Re and molecular Prandtlnumber (Pr). Also an expression for momentum eddy diffusivity is developed. The results revealed that the Prt is less than 0.7 and is function of both Re and Praccording to the following relation: Prt=6.374Re-0.238 Pr-0.161 The capability of many previously proposed models of Prt in predicting the heat transfer coefficient is examined. Cebeci [1973] model is found to give good accuracy when used with the momentum eddy diffusivity developed in the present analysis. The thickness of thermal sublayer decreases with Reynolds number and molecular Prandtl number.